The long memory of equity volatility and the macroeconomy: International evidence - Lena Dräger; Duc Binh Benno Nguyen; Marcel Prokopczuk; Philipp Sibbertsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
This paper examines long memory volatility in international stock markets. We show that long memory volatility is widespread in a panel dataset of eighty-two countries and that the degree of memory in the panel can be related to macroeconomic variables such as short- and long-run interest rates and unemployment. Moreover, we find that developed economies possess longer memory in volatility than emerging and frontier countries and that stock market jumps are negatively correlated with long memory of volatility. Overall, our results provide some evidence of a link between stock market uncertainty and macroeconomic conditions, which is prevalent across a large range of countries.
Keywords: G15; C22; F30; F40; 330; International; Long Memory; Volatility